2012
DOI: 10.1254/jphs.11200sc
|View full text |Cite
|
Sign up to set email alerts
|

The Selective Metabotropic Glutamate 2/3 Receptor Agonist MGS0028 Reverses Isolation Rearing–Induced Abnormal Behaviors in Mice

Abstract: Abstract. Isolation-induced abnormal behaviors are useful animal models for assessing potential anti-psychotic drugs. This study examined the effect of MGS0028, a selective metabotropic glutamate 2/3 receptor agonist, on abnormal behaviors such as hyperactivity, aggression, and deficits of prepulse inhibition in isolation-reared mice. MGS0028 attenuated hyperactivity and aggressive behaviors in isolation-reared mice. The agonist also reversed isolation rearing-induced deficits of prepulse inhibition. On the ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 15 publications
5
19
0
1
Order By: Relevance
“…The data are expressed as the mean ± SEM of 10 mice/group. inhibition in isolation-reared animals (Ago et al, 2012;Maisonnette et al, 1993;Sakaue et al, 2001Sakaue et al, , 2003Sánchez et al, 1993). The present study demonstrated that encounter-induced hyperactivity and increased prefrontal 5-HT levels were blocked by diazepam, osemozotan, and LY379268.…”
Section: Effect Of Encounter Stimulation In Isolated Mice Y Ago Et Alsupporting
confidence: 56%
See 4 more Smart Citations
“…The data are expressed as the mean ± SEM of 10 mice/group. inhibition in isolation-reared animals (Ago et al, 2012;Maisonnette et al, 1993;Sakaue et al, 2001Sakaue et al, , 2003Sánchez et al, 1993). The present study demonstrated that encounter-induced hyperactivity and increased prefrontal 5-HT levels were blocked by diazepam, osemozotan, and LY379268.…”
Section: Effect Of Encounter Stimulation In Isolated Mice Y Ago Et Alsupporting
confidence: 56%
“…However, the mice were able to see, hear, and smell their neighbor. Thus, a social encounter with an unfamiliar conspecific through a mesh partition is considered a form of psychological stress, and it is useful for studies of the neurochemical changes that may be involved in the abnormal behaviors of isolation-reared animals (Ago et al, 2012;Fone and Porkess, 2008;Lukkes et al, 2009a, b;Pinna et al, 2008). In this study, the total time that the resident mice spent near the partition and the total time the resident and intruder mice spent interacting did not differ between the male group-reared, female isolation-reared, and male isolation-reared mice (Figure 1c).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations